Trends in work disability due to mental diagnoses among social workers in Finland and Sweden in 2005-2012. - O. Rantonen; K. Alexanderson; J. Pentti; L. Kjeldgård; J. Hämäläinen; E. Mittendorfer-Rutz; M. Kivimäki; J. Vahtera; P. Salo (Cambridge University Press, 2022)
Social workers report high levels of stress and have an increased risk for hospitalisation with mental diagnoses. However, it is not known whether the risk of work disability with mental diagnoses is higher among social workers compared with other human service professionals. We analysed trends in work disability (sickness absence and disability pension) with mental diagnoses and return to work (RTW) in 2005–2012 among social workers in Finland and Sweden, comparing with such trends in preschool teachers, special education teachers and psychologists.
Records of work disability (>14 days) with mental diagnoses (ICD-10 codes F00–F99) from nationwide health registers were linked to two prospective cohort projects: the Finnish Public Sector study, years 2005–2011 and the Insurance Medicine All Sweden database, years 2005–2012. The Finnish sample comprised 4849 employees and the Swedish 119 219 employees covering four occupations: social workers (Finland 1155/Sweden 23 704), preschool teachers (2419/74 785), special education teachers (832/14 004) and psychologists (443/6726). The reference occupations were comparable regarding educational level. Risk of work disability was analysed with negative binomial regression and RTW with Cox proportional hazards.
Social workers in Finland and Sweden had a higher risk of work disability with mental diagnoses compared with preschool teachers and special education teachers (rate ratios (RR) 1.43–1.91), after adjustment for age and sex. In Sweden, but not in Finland, social workers also had higher work disability risk than psychologists (RR 1.52; 95% confidence interval 1.28–1.81). In Sweden, in the final model special education teachers had a 9% higher probability RTW than social workers. In Sweden, in the final model the risks for work disability with depression diagnoses and stress-related disorder diagnoses were similar to the risk with all mental diagnoses (RR 1.40–1.77), and the probability of RTW was 6% higher in preschool teachers after work disability with depression diagnoses and 9% higher in special education teachers after work disability with stress-related disorder diagnoses compared with social workers.
Social workers appear to be at a greater risk of work disability with mental diagnoses compared with other human service professionals in Finland and Sweden. It remains to be studied whether the higher risk is due to selection of vulnerable employees to social work or the effect of work-related stress in social work. Further studies should focus on these mechanisms and the risk of work disability with mental diagnoses among human service professionals.